Impact of perioperative blood transfusion on gene expression biomarkers in patients with gastrointestinal cancer. Issue 5 (October 2018) - Zhu, Mei; Zhu, Zhijun; Yang, Jizhong; Hu, Kaiming; Li, Yuanhai
Abstract: Objectives: To explore the impacts of perioperative blood transfusion on specific pattern of inflammatory gene expression and nosocomial infections in gastrointestinal cancer patients. Methods: A total of 60 gastrointestinal cancer patients aged over 27 years were recruited, blood transfusion was administered to 30 patients. The peripheral venous blood was drawn from the 30 patients undergoing transfusions and messenger RNA (mRNA) was extracted from PAXGene tubes collected before surgery and at 48 h following the operation. T-helper cell subtype transcription factors were quantified using quantitative real-time polymerase chain reaction. These genes were selected based on their ability to represent specific immune pathways and their expression level of Th1, Th2 and Th17 and the major Treg-specific TFs T-bet, GATA-3, RORγt and FOXP3 were measured. Postoperative infections were documented using predefined criteria. Results: There were significantly lower in Th1-specific TF T-bet ( P < 0.001) mRNA levels and significantly higher in Th2-specifc TF, GATA-3 ( P < 0.001) mRNA levels assayed at 48 h. There was significantly lower in T-bet mRNA/GATA-3 ( P < 0.001) mRNA ratio assayed at 48 h. There were significantly higher in Th17-specific TF RORγt ( P < 0.001) and Treg-specific TF Foxp3 ( P < 0.001) mRNA levels assayed at 48 h. Patients receiving a blood transfusion were more likely to develop postoperative infections ( P = 0.02). Conclusion: There is an association between an immunosuppressive pattern of gene expressions and blood transfusion. This gene expression profile includes a reduction in the activity of T helper cell type 1 (Th1) pathways in those patients receiving a blood transfusion. Furthermore, blood transfusion was associated with an increased susceptibility to nosocomial infections.